Overcoming ultraviolet light instability of sensitized TiO₂ with meso-superstructured organometal tri-halide perovskite solar cells. - Leijtens, T; Eperon, G; Pathak, S; Abate, A; Lee, M; Snaith, H (2013)
The power conversion efficiency of hybrid solid-state solar cells has more than doubled from 7 to 15% over the past year. This is largely as a result of the incorporation of organometallic trihalide perovskite absorbers into these devices. But, as promising as this development is, long-term operational stability is just as important as initial conversion efficiency when it comes to the development of practical solid-state solar cells. Here we identify a critical instability in mesoporous TiO₂-sensitized solar cells arising from light-induced desorption of surface-adsorbed oxygen. We show that this instability does not arise in mesoporous TiO₂-free mesosuperstructured solar cells. Moreover, our TiO₂-free cells deliver stable photocurrent for over 1,000 h continuous exposure and operation under full spectrum simulated sunlight.